Relationship between nonalcoholic fatty liver disease and hyperandrogenemia in adolescents with polycystic ovary syndrome - Ozlem Kara; Hanife Aysegul Arsoy; Murat Keskin (The Korean Pediatric Society, 2023)
Background Nonalcoholic fatty liver disease (NAFLD) is common in adults with polycystic ovary syndrome (PCOS), and several studies on adults have investigated its influencing factors. However, factors associated with NAFLD in adolescents with PCOS remain unknown. Purpose This study aimed to investigate the presence of NAFLD in adolescents with PCOS using the noninvasive methods of vibration-controlled transient elastography (VCTE) and ultrasonography (USG), along with assessing NAFLD-related metabolic and hormonal risk factors. Methods This study included patients aged 12-18 years who were diagnosed with PCOS according to the Rotterdam criteria. The control group included young women with similar age and body mass index (BMI) z scores, who had menstruated regularly for more than 2 years. Patients with PCOS were divided into hyperandrogenemia and nonhyperandrogenemia groups based on serum androgen level. USG was performed on all patients to evaluate the presence of hepatic steatosis. Liver stiffness measurement (LSM) and controlled attenuation parameter (CAP) were assessed using VCTE (Fibroscan). Clinical, laboratory, and radiological data were compared between groups. Results This study included 124 adolescent girls aged 12-18 years (61 with PCOS, 63 controls). BMI z scores were similar between groups. Waist circumference and total cholesterol, triglyceride, and alanine aminotransferase levels were higher in the PCOS versus the control group. The presence of hepatic steatosis on USG was similar between groups. However, the rate of hepatic steatosis on USG was higher in patients with hyperandrogenic PCOS (P=0.01). LSM and CAP measurements were similar between groups. Conclusion No increase in prevalence of NAFLD was observed among adolescents with PCOS. However, hyperandrogenemia is a risk factor for NAFLD. Therefore, adolescents with PCOS and elevated androgen level should be screened for NAFLD.